Integrating irinotecan in standard chemotherapy: A novel dose‐density combination for high‐risk pediatric sarcomas. Issue 7 (10th March 2021) - Bisogno, Gianni; Ferrari, Andrea; Tagarelli, Arianna; Sorbara, Silvia; Chiaravalli, Stefano; Poli, Elena; Scarzello, Giovanni; De Corti, Federica; Casanova, Michela; Affinita, Maria Carmen
Abstract: Background: Irinotecan is a drug active against pediatric sarcomas with a toxicity profile that theoretically allows for its association with more myelotoxic drugs. We examined the feasibility of a dose‐density strategy integrating irinotecan in standard chemotherapy regimens for patients with high‐risk sarcomas. Methods: Between November 2013 and January 2020, 23 patients ≤25 years old were included in the study. Eleven patients newly diagnosed with metastatic disease received nine cycles of IrIVA (irinotecan‐ifosfamide‐vincristine‐actinomycin D; ifosfamide 3 g/m 2 on days 1 and 2, vincristine 1.5 mg/m 2 on day 1, actinomycin D 1.5 mg/m 2 on day 1, irinotecan 20 mg/m 2 for 5 consecutive days starting on day 8) as first‐line therapy. Two relapsed patients received IrIVA and 10 IrVAC (irinotecan‐vincristine‐actinomycin D‐cyclophosphamide; cyclophosphamide 1.5 g/m 2 on day 1 instead of ifosfamide). Feasibility was assessed in terms of toxicity and time to complete the treatment. Results: Seventeen rhabdomyosarcomas, four Ewing sarcomas, two desmoplastic small round cell tumors received a total of 181 cycles (range 2–10). Grade 4 neutropenia occurred in 62.4% of the cycles. Thirteen patients had febrile neutropenia. Diarrhea occurred in 14 cycles. The median time to complete the treatment was 195 days (range 170–231), 83.4% of cycles were administered on time or with a delay <1 week. With a median follow‐up of 2.6 years (range 0.2–5.0), 12 patients are alive, nine complete remissions, three with the disease. Conclusions: A dose‐density strategy combining irinotecan with standard chemotherapy is feasible. This approach will be investigated in the next trial coordinated by the European pediatric Soft tissue sarcoma Study Group.